Gerakan Muhammadiyah Sebagai Agen Reformasi Pendidikan Islam Di Indonesia - Delsa Dwi Arini; Aulia Suzan; Idrus L (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of Muhammadiyah as an agent of Islamic education reform in Indonesia through an empirical mixed-methods approach integrating qualitative and quantitative data. The research employs a convergent parallel design to analyze theological foundations of tajdid, institutional dynamics, and the socio-cultural impact of Muhammadiyah’s educational system. Findings reveal that Muhammadiyah successfully integrates religious and general knowledge through a value-based educational framework supported by strong institutional networks and adaptive governance. Quantitative results indicate high levels of perceived effectiveness in character formation, ethical development, and social engagement among learners, while qualitative insights highlight the importance of institutional culture in sustaining reform. The study also identifies Muhammadiyah’s contribution to social empowerment, gender inclusion, and global competitiveness of graduates. These findings suggest that Muhammadiyah represents a sustainable model of progressive Islamic education that combines theological renewal, institutional capacity, and socio-cultural engagement, offering a relevant framework for broader educational reform in Muslim societies.